Fatores envolvidos no processo de ensino-aprendizagem de estudantes mais velhos e professores/funcionários em cursos técnicos na área de saúde no SENAC de Itapetininga/SP em tempos de ensino remoto - Souza, Elenil Gozzo de (2021)
Education has become dependent on digital information and communication technologies; this situation has been called the “Fourth Industrial Revolution”. This universal trend was catalyzed by the COVID-19 Pandemic process, as it was necessary to accelerate digital technological adhesion to allow the continuity of the teaching/learning process remotely, in order to respect the principle of social isolation and the progress of the courses. There are sectors whose clientele already had some difficulty in using these technologies, precisely because they do not have the skills and familiarity with digital processes. This is what usually happens with older students. The general objective of this research was to seek to assess the difficulties in the teaching/learning process of students from Technical Courses in the Areas of Health and Welfare at SENAC – Itapetininga, with regard to the use of digital information technologies. Methodology: this is an investigative, transversal, quantitative work carried out in a real field, approaching the entire group involved in the process, based on anonymous questionnaire responses, answered through the Google FORMS Platform. Statistical analysis was obtained with SPSS /IBM (Statistical Package for the Social Sciences/International Business Machines Corporation). Results: The study included 101 students from the courses of Nursing, Aesthetics, Massage Therapy, Pharmacy and Elderly Caregivers, 26 professors and 16 administrative technical staff from SENACItapetininga. Conclusion: The survey showed a disagreement between what the respondent students and teachers/staff considered about difficulties in remote classroom practices, with older students reported having no difficulty in remote learning and teachers stated that the Difficulty exists and this is found in the handling of digital devices